Correction to: Modeling mortality risk effects of cigarettes and smokeless tobacco: results from the national health interview survey linked mortality file data - Esther Salazar; Chunfeng Ren; Brian L. Rostron; Ghideon Solomon (BMC, 2022)
An amendment to this paper has been published and can be accessed via the original article.